Site‐Specific Mutations on KRAS, NRAS, and BRAF Corelate With the Frequency of ctDNA in Colorectal Cancer - Fumihiro Yoshimura; Yoichiro Yoshida; Teppei Yamada; Keita Tanaka; Takaomi Hayashi; Hideki Shimaoka; Ryohei Sakamoto; Naoya Aisu; Gumpei Yoshimatsu; Suguru Hasegawa (Cancer Reports, 2025)
ABSTRACT Background Early prediction of metastatic risk after tumor resection for colorectal cancer (CRC) is critical to improve treatment outcomes. Although circulating tumor DNA (ctDNA) is an important biomarker in CRC patients, positivity is variable because cutoff values for each gene have not been clearly established. When examining the mutant allele frequency (MAF) of a gene, the cutoff value is the same for the same gene, even if the mutation sites are different. In this study, we examined the relationship between MAF and the genetic mutation site and factors that influence the prediction of recurrence by ctDNA. Methods This study included 422 CRC patients who underwent surgery. ctDNA was sampled from blood samples of 102 CRC patients with KRAS, NRAS, and BRAF mutations and analyzed using the digital polymerase chain reaction system. Preoperative, postoperative day 1, postoperative day 7, and postoperative day 30 MAF were examined for each gene mutation site. Results Kruskal–Wallis test revealed significant differences in MAF between mutated codon sites at all MAF assessment times (p < 0.001). The MAF values of KRAS codon 146 at all time points were significantly higher than for the other mutation sites. Steel‐Dwass tests revealed KRAS codon 146 had significantly higher MAF values than KRAS codons 12 and 13 on all blood collection dates. Similarly, BRAF codon 600 had significantly higher MAF values than KRAS codon 12 on all blood collection dates. Conclusions This study revealed that MAF values differed significantly depending on the site of mutation, even for the same gene. These results suggest that MAF cutoff values may need to be established for each gene mutation site.